Kebijakan Tentang Pengembangan Lembaga Pendidikan Islam Non-Formal: Madrasah Diniyah Takmiliyah (MDT) Tahun 2011-2015 - Noblana Adib (Sustainable, 2019)
The more autonomous the more creative. This article refutes Hasbullah's opinion that the management of Madrasas is not autonomous because it is under the centralized Ministry of Religion (Kemenag). Hasbullah said that it was very dilemmatic, Madrasas could not develop because in the budget structure in the area of Islamic education institutions were not included in the local government budget (APBD) otherwise the ministry of religion did not have an adequate budgeting structure to finance all educational institutions under its guidance. Instead of Madrasas being marginalized institutions at the local level, madrasas are the concern of several local governments committed to helping, especially the implement. Keyword : Madrasah Diniyah Takmiliyah, Educational Policy, Islamic educational institutions Abstrak Semakin otonom semakin kreatif. Artikel ini membantah pendapat Hasbullah yang mengemukakan pengelolaan Madrasah yang tidak diotonomkan sebab di bawah Kementerian Agama (Kemenag) yang masih sentralisasi. Hasbullah mengatakan sangat dilematis, Madrasah tidak dapat berkembang karena dalam struktur anggaran di daearah lembaga pendidikan Islam tidak masuk di APBD (anggaran pemerintah daerah) sebaliknya kementerian agama tidak punya struktur penganggaran yang memadai untuk membiayai seluruh lembaga pendidikan yang berada di bawah binaannya. Alih-alih Madrasah menjadi lembaga yang termarginalisasi di tingkat daerah, madrasah menjadi perhatian beberapa pemerintah daerah berkomitmen membantu, terutama penyelenggaraan MDT sebagaimana yang kemukakan oleh Juju Saepudin, Amin Thaib BR, Abdul Basid, Nursalamah Siagian, dan Neneng Habibah.